A composite membrane material for oil-water separation and a preparation method thereof

By pretreating activated carbon and modifying MOF materials, combined with tannic acid modification, a composite membrane material was prepared, which solved the problems of easy clogging and insufficient mechanical strength of PVA membranes, and achieved efficient and durable oil-water separation effect.

CN120860827BActive Publication Date: 2025-12-09YANGZHOU POLYTECHNIC INST
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511394513.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-28
Publication Date
2025-12-09
Estimated Expiration
2045-09-28

AI Technical Summary

Technical Problem

Existing PVA membranes are prone to clogging and lack mechanical strength in the treatment of high-concentration oily wastewater. Traditional oil-water separation methods are inefficient, energy-intensive, or cause secondary pollution. The water flux of existing modified PVA hydrogel oil-water separation materials needs to be improved.

Method used

By pretreating activated carbon to increase oxygen-containing groups and grafting amino groups with an aminosilane coupling agent, an activated carbon/MOF composite material was prepared. This material was then modified with tannic acid to form a composite modified activated carbon material, which was then loaded onto a PVA fiber membrane and crosslinked to form a composite membrane material with an optimized pore structure.

Benefits of technology

It improves the hydrophilicity and oleophobicity of the membrane, enhances the oil-water separation efficiency and mechanical strength, achieves efficient oil-water separation and extends the service life of the membrane, and has good self-cleaning ability and high separation efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120860827B_ABST
    Figure CN120860827B_ABST
Patent Text Reader

Abstract

The application relates to the technical field of film material preparation, and particularly discloses a composite film material for oil-water separation and a preparation method thereof. The MOF material is loaded on the surface and pore structure of activated carbon, the pore structure of the activated carbon is optimized, and the oil-water separation efficiency is improved. Meanwhile, the MOF material of the iron and lanthanum bimetallic ligand has better hydrophilicity compared with single metal MOF material. Fe 3+ forms strong coordination with water molecules, constructs a hydration layer on the MOF surface, and blocks oil molecules from contacting. 3+ La 3+ has strong polarization and can induce the directional arrangement of polar molecules in oil droplets, weakens the stability of the oil droplets, promotes demulsification, and further improves the oil-water separation efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of film material preparation, in particular to a composite film material for oil-water separation and a preparation method thereof. BACKGROUND

[0002] In the field of oily wastewater treatment, traditional methods mainly include gravity separation, air flotation, centrifugal separation and chemical demulsification. Gravity separation utilizes the density difference between oil and water to achieve layering, which is suitable for the removal of large particle floating oil, but the treatment effect on emulsified oil is limited; air flotation improves separation efficiency by adsorbing oil droplets with micro-bubbles, but has high energy consumption and is prone to secondary pollution; centrifugal separation can efficiently separate small oil droplets, but the equipment maintenance cost is high; chemical demulsification destroys the emulsion system by adding reagents, but may introduce new pollutants. These methods generally have low efficiency, high energy consumption or secondary pollution, and are difficult to meet the increasingly stringent environmental protection requirements.

[0003] Polyvinyl alcohol (PVA) membranes are widely used in oily wastewater treatment due to their hydrophilicity and film-forming property, but existing PVA membranes still have significant defects. Although their high hydrophilicity can block oil droplets, the membrane pores are easily clogged by oil stains after long-term use, resulting in a sharp decrease in flux; at the same time, PVA molecular chains are easily swollen in humid environments, significantly reducing the mechanical strength and affecting the stability of the membrane structure. These limitations limit the application of PVA membranes in high-concentration oily wastewater or complex working conditions, and performance breakthroughs are urgently needed through material modification and structure design.

[0004] Chinese patent document CN202110791633.9 discloses an oil-water separation material based on electrospun / PVA composite hydrogel and its preparation method and application. PVA, PAN and PMMA solutions are spun into fiber membranes by electrospinning technology, and the modified PVA hydrogel is used to functionalize and modify the fiber membranes. After freeze-thaw, the cross-linked PVA hydrogel is coated on the surface of the fiber membranes to form an electrospun / PVA hydrogel separation material with hydrophilic and oleophobic properties for oil-water separation, but the water flux of the prepared oil-water separation material still needs to be further improved. SUMMARY

[0005] In view of the deficiencies of the prior art, the present application aims to provide a composite film material for oil-water separation and a preparation method thereof.

[0006] To achieve the above-mentioned purpose, the present application adopts the following technical solutions:

[0007] A preparation method of a composite film material for oil-water separation, comprising the following steps:

[0008] S1, preparing amino-modified activated carbon

[0009] The pretreated activated carbon is dispersed in an ethanol aqueous solution, and then an amino silane coupling agent is added thereto, and stirring treatment is performed, followed by filtration, washing, and drying to obtain the amino-modified activated carbon.

[0010] In this step, the pretreated activated carbon is prepared by immersing the activated carbon in a nitric acid solution, and performing heating and stirring treatment, followed by washing and drying.

[0011] Specifically, the concentration of the nitric acid solution is 0.5-3 mol / L, for example, 0.5 mol / L, 1 mol / L, 1.5 mol / L, 2 mol / L, 2.5 mol / L, or 3 mol / L, but is not limited to the listed values, and other values not listed in the range are also applicable.

[0012] Specifically, the temperature of the heating and stirring treatment is 60-80℃, for example, 60℃, 65℃, 70℃, 75℃, or 80℃, and the time of the heating and stirring treatment is 2-5 h, for example, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, or 5 h, but is not limited to the listed values, and other values not listed in the range are also applicable.

[0013] In this step, the mass ratio of the pretreated activated carbon to the amino silane coupling agent is 4-8:1-2, for example, 4:1, 4:2, 6:1, 6:2, 8:1, or 8:2, but is not limited to the listed values, and other values not listed in the range are also applicable.

[0014] Specifically, the amino silane coupling agent is selected from KH550, N-β-aminoethyl-γ-aminopropyltrimethoxysilane, or diethylaminomethyltriethoxysilane.

[0015] In this step, the number of oxygen-containing groups such as hydroxyl and carboxyl groups on the surface of the activated carbon is increased by pretreating the activated carbon, and then the amino silane coupling agent is used to graft amino groups (-NH2) onto the surface of the activated carbon through hydrolysis and condensation reaction of the alkoxy groups of the amino silane coupling agent with the hydroxyl groups on the surface of the activated carbon, so that the amino groups can be used as coordination sites to combine with metal ions (such as Fe 3+ , La 3+ ), thereby improving the anchoring ability of the MOF material on the surface of the activated carbon.

[0016] S2, preparation of activated carbon / MOF composite material

[0017] The iron salt, the lanthanum salt, and the organic ligand are dissolved in an organic solvent, and then the amino-modified activated carbon is added thereto, and ultrasonic dispersion is performed until uniform, and then hydrothermal reaction is performed, and after the reaction is completed, centrifugation, washing, and drying are performed to obtain the activated carbon / MOF composite material.

[0018] In this step, the amount ratio of the iron salt, lanthanum salt, organic ligand and amino-modified activated carbon is 1-2 mmol: 0.2-0.5 mmol: 2-4 mmol: 2-5 g.

[0019] Specifically, the iron salt is selected from ferric chloride or ferric nitrate.

[0020] Specifically, the lanthanum salt is selected from lanthanum chloride or lanthanum nitrate.

[0021] Specifically, the organic ligand is selected from terephthalic acid or 2-amino terephthalic acid.

[0022] In this step, the temperature of the hydrothermal reaction is 150-180℃, for example, 150℃, 155℃, 160℃, 165℃, 170℃, 175℃, 180℃ can be selected; the time of the hydrothermal reaction is 4-8h, for example, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h can be selected, but is not limited to the listed values, other values not listed in the value range are also applicable.

[0023] In this step, by loading the MOF material on the surface and pore structure of the activated carbon, the pore structure of the activated carbon is optimized, so that water molecules can easily pass through, while macromolecular oil stains cannot easily pass through, thereby improving the oil-water separation efficiency; at the same time, by forming the MOF material of the iron and lanthanum bimetallic ligand, compared with the single metal MOF material, it has better hydrophilicity, wherein Fe 3+ forms strong coordination with water molecules, constructs a hydration layer on the surface of the MOF, and blocks the contact of oil molecules; La 3+ has a strong affinity for oxygen atoms, can anchor more water molecules, and further improves the hydrophilicity of the MOF material, La 3+ strong polarization effect can induce the directional arrangement of polar molecules in the oil droplets, weaken the stability of the oil droplets, promote demulsification, and further improve the oil-water separation efficiency, La 3+ rigid coordination can effectively prevent Fe 3+ from dissolving out, so that the composite membrane material can be recycled.

[0024] S3, preparing a composite modified activated carbon material

[0025] After the activated carbon / MOF composite material and the tannic acid solution are uniformly mixed, ball milling treatment is performed to obtain a composite modified activated carbon material.

[0026] In this step, the mass ratio of the activated carbon / MOF composite material and the tannic acid solution is 10-15:20-30, for example, 10:20, 10:25, 10:30, 12:20, 12:25, 12:30, 15:20, 15:25, 15:30 can be selected, but not limited to the listed values, and other values not listed in the value range are also applicable.

[0027] Specifically, the mass fraction of the tannic acid solution is 2-5%, for example, 2%, 3%, 4%, 5% can be selected, but not limited to the listed values, and other values not listed in the value range are also applicable.

[0028] In this step, the rotation speed of the ball milling treatment is 200-400 r / min, and the ball milling treatment time is 2-4 h.

[0029] In this step, the surface of the activated carbon / MOF composite material is modified by using tannic acid, which enhances the dispersion performance of the activated carbon / MOF composite material in the PVA solution, and also improves the hydrophilicity and underwater oleophobicity of the activated carbon / MOF composite material, which is beneficial to improve the oil-water separation efficiency.

[0030] S4, preparing a fiber membrane

[0031] The PVA solution is prepared, and then the composite modified activated carbon material is added and uniformly dispersed by ultrasonic, followed by electrospinning to obtain a fiber membrane.

[0032] In this step, the amount ratio of the PVA solution and the composite modified activated carbon material is 10 mL:0.01-0.1 g. For example, 10 mL:0.01 g, 10 mL:0.02 g, 10 mL:0.03 g, 10 mL:0.04 g, 10 mL:0.05 g, 10 mL:0.06 g, 10 mL:0.07 g, 10 mL:0.08 g, 10 mL:0.09 g, 10 mL:0.1 g can be selected, but not limited to the listed values, and other values not listed in the value range are also applicable.

[0033] Specifically, the mass fraction of the PVA solution is 5-10%, for example, 5%, 6%, 7%, 8%, 9%, 10% can be selected, but not limited to the listed values, and other values not listed in the value range are also applicable.

[0034] S5, preparing a composite membrane material

[0035] The fiber membrane is placed in glutaraldehyde vapor for crosslinking to obtain a composite membrane material for oil-water separation.

[0036] The specific steps of cross-linking in glutaraldehyde vapor in this step are as follows: a mixed solution is obtained by mixing glutaraldehyde solution and concentrated hydrochloric acid according to a volume ratio of 3:1, the mixed solution is placed in the lower part of a dryer, the fiber membrane is laid on a ceramic plate, the system is kept in a closed state, a glutaraldehyde vapor atmosphere is formed, and cross-linking is carried out at room temperature for 48h, so that the composite membrane material is obtained.

[0037] Specifically, the mass fraction of the used glutaraldehyde solution is 25%, and the mass fraction of the concentrated hydrochloric acid is 37%.

[0038] In this step, the aldehyde group of glutaraldehyde reacts with the hydroxyl group of PVA and the phenolic hydroxyl group of tannic acid to form a covalent cross-linking network, and glutaraldehyde may react with the uncoordinated amino group in MOF to improve the water resistance and mechanical strength of the composite membrane material, avoid disintegration when used underwater, and improve the service life of the membrane material.

[0039] The application also provides a composite membrane material for oil-water separation prepared by the preparation method.

[0040] Compared with the prior art, the application has the following beneficial effects:

[0041] (1) In the application, the activated carbon is pretreated first, so that the number of oxygen-containing groups such as hydroxyl groups and carboxyl groups on the surface of the activated carbon is increased, then the hydrolysis condensation reaction of the alkoxy group of the amino silane coupling agent and the hydroxyl group on the surface of the activated carbon is carried out, and the amino group (-NH2) is grafted to the surface of the activated carbon, so that the amino group can be combined with metal ions (such as Fe 3+ , La 3+ ) as a coordination site, and the anchoring ability of the MOF material on the surface of the activated carbon is improved.

[0042] (2) In the application, the MOF material is loaded on the surface and pore structure of the activated carbon, the pore structure of the activated carbon is optimized, so that water molecules can easily pass through, but macromolecular oil stains cannot easily pass through, and the oil-water separation efficiency is improved; and the MOF material in the form of a double metal ligand of iron and lanthanum has better hydrophilicity than a single metal MOF material, in which Fe 3+ forms a strong coordination with water molecules to construct a hydration layer on the surface of the MOF material to block the contact of oil molecules; La 3+ has a strong affinity for oxygen atoms and can anchor more water molecules, so that the hydrophilicity of the MOF material is further improved, the strong polarization of La 3+ can induce the directional arrangement of polar molecules in oil droplets, so that the stability of the oil droplets is weakened, the demulsification is promoted, the oil-water separation efficiency is further improved, and the rigidity coordination of La 3+ can effectively prevent Fe 3+ from dissolving, so that the composite membrane material can be recycled.

[0043] (3) The application enhances the dispersion performance of the activated carbon / MOF composite material in the PVA solution by using tannic acid to modify the surface of the activated carbon / MOF composite material, and improves the hydrophilicity and underwater oleophobicity of the activated carbon / MOF composite material, which is conducive to improving the oil-water separation efficiency. BRIEF DESCRIPTION OF DRAWINGS

[0044] Figure 1 The electron microscope image of the composite film material prepared in Example 1;

[0045] Figure 2 The self-cleaning performance schematic diagram of the composite film material prepared in Example 1;

[0046] Figure 3 The schematic diagram of the device for oil-water separation test;

[0047] Figure 4 The actual effect comparison diagram before and after the oil-in-water emulsion separation. DETAILED DESCRIPTION

[0048] The application will be further described in detail through specific preferred embodiments, but the application is not limited to the following embodiments.

[0049] It should be noted that, unless otherwise specified, the chemical reagents involved in the application are purchased through commercial channels.

[0050] The mesh number of the activated carbon used in the embodiments of the application is 400 mesh;

[0051] The type of polyvinyl alcohol is PVA1788;

[0052] The mass fraction of glutaraldehyde solution is 25%, and the mass fraction of concentrated hydrochloric acid is 37%.

[0053] Example 1

[0054] A preparation method of a composite film material for oil-water separation, comprising the following steps:

[0055] S1, 10g of activated carbon is immersed in 100mL of 1mol / L nitric acid solution, heated and stirred at 80℃ for 2h, washed and dried to obtain pretreated activated carbon;

[0056] S2, 5g of pretreated activated carbon is dispersed in 100mL of 75wt% ethanol aqueous solution, then 1g of KH550 is added, stirred at room temperature for 2h, and then filtered, washed and dried to obtain amino-modified activated carbon;

[0057] S3, 1 mmol of FeCl3·6H2O, 0.2 mmol of La(NO3)3·6H2O and 2 mmol of p-phenylenediamine were dissolved in 25 mL of organic solvent DMF, then 3 g of amino-modified activated carbon was added and uniformly dispersed by ultrasonic, and the hydrothermal reaction was carried out at 150℃ for 8 h. After the reaction was completed, centrifugation, washing and drying were carried out to obtain the activated carbon / MOF composite material;

[0058] S4, 10 g of activated carbon / MOF composite material and 20 g of 3 wt% tannic acid solution were uniformly mixed and then subjected to ball milling treatment at a speed of 400 r / min for 2 h. After ball milling, drying was carried out to obtain the composite modified activated carbon material;

[0059] S5, 10 mL of 8 wt% PVA solution was prepared, then 0.05 g of composite modified activated carbon material was added and uniformly dispersed by ultrasonic, and then injected into a 10 ml syringe. A 21G (needle inner diameter of 0.51 mm) stainless steel needle was fixed in the syringe, the roller speed was set to 120 r / min, the needle to roller distance was 15 cm, the working voltage was 10 KV, and the spinning rate was 0.008 mm / s. After spinning, the formed fiber membrane was collected from the roller and placed in a blast drying oven at 60℃ for 2 h to obtain the fiber membrane.

[0060] S6, a mixed solution was obtained by mixing glutaraldehyde solution and concentrated hydrochloric acid at a volume ratio of 3:1, and the mixed solution was placed in the lower part of the dryer. The fiber membrane was laid on the ceramic plate, and the system was kept in a closed state to form a glutaraldehyde vapor atmosphere. Crosslinking was carried out at room temperature for 48 h to obtain the composite membrane material for oil-water separation.

[0061] Example 2

[0062] A preparation method of a composite membrane material for oil-water separation, comprising the following steps:

[0063] S1, 10 g of activated carbon was immersed in 100 mL of 1 mol / L nitric acid solution and heated and stirred at 80℃ for 2 h. After washing and drying, the pretreated activated carbon was obtained.

[0064] S2, 5 g of pretreated activated carbon was dispersed in 100 mL of 75 wt% ethanol aqueous solution, then 1 g of KH550 was added and stirred at room temperature for 2 h. After filtration, washing and drying, the amino-modified activated carbon was obtained.

[0065] S3, 1 mmol of FeCl3·6H2O, 0.2 mmol of La(NO3)3·6H2O and 2 mmol of p-phenylenediamine were dissolved in 25 mL of organic solvent DMF, then 3 g of amino-modified activated carbon was added and uniformly dispersed by ultrasonic, and the hydrothermal reaction was carried out at 150℃ for 8 h. After the reaction was completed, centrifugation, washing and drying were carried out to obtain the activated carbon / MOF composite material;

[0066] S4, 10 g of activated carbon / MOF composite material and 20 g of 3 wt% tannic acid solution were uniformly mixed and then subjected to ball milling treatment at a speed of 400 r / min for 2 h. After ball milling, drying was carried out to obtain the composite modified activated carbon material;

[0067] S5, 10 mL of 8 wt% PVA solution was prepared, then 0.025 g of composite modified activated carbon material was added and uniformly dispersed by ultrasonic, and then injected into a 10 ml syringe. A 21G (needle inner diameter of 0.51 mm) stainless steel needle was fixed in the syringe, the roller speed was set to 120 r / min, the needle to roller distance was 15 cm, the working voltage was 10 KV, and the spinning rate was 0.008 mm / s. After spinning, the formed fiber membrane was collected from the roller and placed in a blast drying oven at 60℃ for 2 h to obtain the fiber membrane.

[0068] S6, a mixed solution was obtained by mixing glutaraldehyde solution and concentrated hydrochloric acid at a volume ratio of 3:1, and the mixed solution was placed in the lower part of the dryer. The fiber membrane was laid on the ceramic plate, and the system was kept in a closed state to form a glutaraldehyde vapor atmosphere. Crosslinking was carried out at room temperature for 48 h to obtain the composite membrane material for oil-water separation.

[0069] Example 3

[0070] A preparation method of a composite membrane material for oil-water separation, comprising the following steps:

[0071] S1, 10 g of activated carbon was immersed in 100 mL of 1 mol / L nitric acid solution, heated and stirred at 80℃ for 2 h, and then washed and dried to obtain the pretreated activated carbon;

[0072] S2, 5 g of pretreated activated carbon was dispersed in 100 mL of 75 wt% ethanol aqueous solution, then 1 g of KH550 was added and stirred at room temperature for 2 h, and then filtered, washed and dried to obtain the amino-modified activated carbon;

[0073] S3, 1 mmol FeCl3·6H2O, 0.2 mmol La(NO3)3·6H2O and 2 mmol terephthalic acid were dissolved in 25 mL of organic solvent DMF, then 3 g of amino-modified activated carbon was added and uniformly dispersed by ultrasonic, and then hydrothermal reaction was carried out at 150℃ for 8 h; after the reaction was completed, centrifugation, washing and drying were carried out to obtain an activated carbon / MOF composite material;

[0074] S4, 10 g of activated carbon / MOF composite material and 20 g of 3 wt% tannic acid solution were uniformly mixed and then subjected to ball milling treatment at a speed of 400 r / min for 2 h; after the ball milling treatment, drying was carried out to obtain a composite modified activated carbon material;

[0075] S5, 10 mL of 8 wt% PVA solution was prepared, then 0.1 g of the composite modified activated carbon material was added and uniformly dispersed by ultrasonic, and then injected into a 10 ml syringe; a 21G (inner diameter of needle is 0.51 mm) stainless steel needle was fixed in the syringe, the roller speed was set to 120 r / min, the distance between the needle and the roller was 15 cm, the working voltage was 10 KV, and the spinning rate was 0.008 mm / s; after the spinning was completed, the formed fiber membrane was collected from the roller and placed in a blast drying oven for drying at 60℃ for 2 h to obtain a fiber membrane.

[0076] S6, a mixed solution was obtained by mixing glutaraldehyde solution and concentrated hydrochloric acid at a volume ratio of 3:1, and the mixed solution was placed in the lower part of a dryer; the fiber membrane was laid on a ceramic plate, and the system was kept in a closed state to form a glutaraldehyde vapor atmosphere; crosslinking was carried out at room temperature for 48 h to obtain a composite membrane material for oil-water separation.

[0077] Comparative Example 1

[0078] A preparation method of a PVA membrane material for oil-water separation, comprising the following steps:

[0079] S1, 10 g of activated carbon was immersed in 100 mL of 1 mol / L nitric acid solution, heated and stirred at 80℃ for 2 h, and then washed and dried to obtain a pretreated activated carbon;

[0080] S2, 10 mL of 8 wt% PVA solution was prepared, then 0.05 g of the pretreated activated carbon was added and uniformly dispersed by ultrasonic, and then injected into a 10 ml syringe; a 21G (inner diameter of needle is 0.51 mm) stainless steel needle was fixed in the syringe, the roller speed was set to 120 r / min, the distance between the needle and the roller was 15 cm, the working voltage was 10 KV, and the spinning rate was 0.008 mm / s; after the spinning was completed, the formed fiber membrane was collected from the roller and placed in a blast drying oven for drying at 60℃ for 2 h to obtain a fiber membrane.

[0081] S2, glutaraldehyde solution and concentrated hydrochloric acid were mixed in a ratio of 3:1, and a mixed solution was obtained. The mixed solution was placed in the lower part of the dryer, the fiber membrane was laid on the ceramic plate, and the system was kept closed to form a glutaraldehyde vapor atmosphere. The crosslinking was carried out at room temperature for 48 h to obtain a PVA membrane material for oil-water separation.

[0082] In the comparative example 1, the pretreated activated carbon was not modified.

[0083] Comparative example 2

[0084] A preparation method of a composite membrane material for oil-water separation comprises the following steps:

[0085] S1, 10 g of activated carbon was immersed in 100 mL of 1 mol / L nitric acid solution and heated and stirred at 80°C for 2 h. After washing and drying, pretreated activated carbon was obtained.

[0086] S2, 5 g of pretreated activated carbon was dispersed in 100 mL of 75 wt% ethanol aqueous solution, and then 1 g of KH550 was added. The mixture was stirred at room temperature for 2 h. After filtration, washing and drying, amino-modified activated carbon was obtained.

[0087] S3, 1 mmol of FeCl3·6H2O and 2 mmol of terephthalic acid were dissolved in 25 mL of organic solvent DMF, and then 3 g of amino-modified activated carbon was added. The mixture was uniformly dispersed by ultrasonic, and then hydrothermal reaction was carried out at 150°C for 8 h. After the reaction was completed, the mixture was centrifuged, washed and dried to obtain an activated carbon / MOF composite material.

[0088] S4, 10 g of activated carbon / MOF composite material and 20 g of 3 wt% tannic acid solution were mixed uniformly and then subjected to ball milling treatment at a speed of 400 r / min for 2 h. After ball milling, the mixture was dried to obtain a composite modified activated carbon material.

[0089] S5, 10 mL of 8 wt% PVA solution was prepared, and then 0.05 g of composite modified activated carbon material was added. The mixture was uniformly dispersed by ultrasonic, and then injected into a 10 ml syringe. A 21G (needle inner diameter of 0.51 mm) stainless steel needle was fixed in the syringe. The roller speed was set to 120 r / min, the needle to roller distance was 15 cm, the working voltage was 10 KV, and the spinning rate was 0.008 mm / s. After spinning, the formed fiber membrane was collected from the roller and dried in a blast drying oven at 60°C for 2 h to obtain a fiber membrane.

[0090] S6, glutaraldehyde solution and concentrated hydrochloric acid volume ratio of 3:1 is mixed, the mixed solution is placed in the lower part of the dryer, the fiber membrane is laid on the ceramic plate, the system is kept closed, a glutaraldehyde vapor atmosphere is formed, and the crosslinking is carried out at room temperature for 48 h, so that the composite membrane material for oil-water separation is obtained.

[0091] In the step S3, La(NO3)3·6H2O is not added in the comparative example 2 compared with the example 1.

[0092] Comparative example 3

[0093] A preparation method of a composite membrane material for oil-water separation comprises the following steps:

[0094] S1, 10 g of activated carbon is immersed in 100 mL of 1 mol / L nitric acid solution, heated and stirred at 80℃ for 2 h, washed and dried to obtain a pretreated activated carbon;

[0095] S2, 5 g of the pretreated activated carbon is dispersed in 100 mL of 75 wt% ethanol aqueous solution, then 1 g of KH550 is added, stirred at room temperature for 2 h, and then filtered, washed and dried to obtain an amino-modified activated carbon;

[0096] S3, 0.2 mmol of La(NO3)3·6H2O and 2 mmol of terephthalic acid are dissolved in 25 mL of organic solvent DMF, then 3 g of the amino-modified activated carbon is added and ultrasonically dispersed, and then hydrothermal reaction is carried out at 150℃ for 8 h, after the reaction is completed, centrifugation, washing and drying are carried out to obtain an activated carbon / MOF composite material;

[0097] S4, 10 g of the activated carbon / MOF composite material and 20 g of 3 wt% tannic acid solution are uniformly mixed and subjected to ball milling treatment, the rotation speed of the ball milling treatment is 400 r / min, the ball milling treatment time is 2 h, and after the ball milling is completed, drying is carried out to obtain a composite modified activated carbon material;

[0098] S5, 10 mL of 8 wt% PVA solution is prepared, then 0.05 g of the composite modified activated carbon material is added and ultrasonically dispersed, a 10 ml syringe is used, a 21G (needle inner diameter is 0.51 mm) stainless steel needle is fixed in the syringe, the roller rotation speed is set to 120 r / min, the needle to roller distance is 15 cm, the working voltage is 10 KV, the spinning rate is 0.008 mm / s, after the spinning is completed, the formed fiber membrane is collected from the roller and placed in a blast drying oven for drying at 60℃ for 2 h to obtain a fiber membrane.

[0099] S6, glutaraldehyde solution and concentrated hydrochloric acid volume ratio of 3:1 is mixed, the mixed solution is placed in the lower part of the dryer, the fiber membrane is laid on the ceramic plate, the system is kept closed, a glutaraldehyde vapor atmosphere is formed, and the crosslinking is carried out at room temperature for 48 h, so that the composite membrane material for oil-water separation is obtained.

[0100] In the comparative example 3, FeCl3·6H2O is not added in step S3.

[0101] Comparative example 4

[0102] A preparation method of a composite membrane material for oil-water separation comprises the following steps:

[0103] S1, 10 g of activated carbon is immersed in 100 mL of 1 mol / L nitric acid solution, heated and stirred at 80°C for 2 h, and then washed and dried to obtain a pretreated activated carbon;

[0104] S2, 5 g of the pretreated activated carbon is dispersed in 100 mL of 75 wt% ethanol aqueous solution, then 1 g of KH550 is added, stirred at room temperature for 2 h, and then filtered, washed and dried to obtain an amino-modified activated carbon;

[0105] S3, 1 mmol of FeCl3·6H2O, 0.2 mmol of La(NO3)3·6H2O and 2 mmol of terephthalic acid are dissolved in 25 mL of organic solvent DMF, then 3 g of the amino-modified activated carbon is added and ultrasonically dispersed, and then hydrothermal reaction is carried out at 150°C for 8 h, after the reaction is completed, centrifugation, washing and drying are carried out to obtain an activated carbon / MOF composite material;

[0106] S4, 10 mL of 8 wt% PVA solution is prepared, then 0.05 g of the activated carbon / MOF composite material is added and ultrasonically dispersed, a 10 ml syringe is filled, a 21G (needle inner diameter is 0.51 mm) stainless steel needle is fixed in the syringe, the roller rotation speed is set to 120 r / min, the distance between the needle and the roller is 15 cm, the working voltage is 10 KV, and the spinning rate is 0.008 mm / s, after the spinning is completed, the formed fiber membrane is collected from the roller and placed in a blast drying oven for drying at 60°C for 2 h to obtain a fiber membrane.

[0107] S5, glutaraldehyde solution and concentrated hydrochloric acid volume ratio of 3:1 is mixed, the mixed solution is placed in the lower part of the dryer, the fiber membrane is laid on the ceramic plate, the system is kept closed, a glutaraldehyde vapor atmosphere is formed, and the crosslinking is carried out at room temperature for 48 h, so that the composite membrane material for oil-water separation is obtained.

[0108] Compared with Example 1, Comparative Example 4 did not involve ball milling of the activated carbon / MOF composite material with tannic acid solution.

[0109] The electron micrograph of the composite membrane material prepared in Example 1 of this invention is shown below. Figure 1 As shown in the figure, the composite membrane material prepared by the present invention has straight and uniform membrane fibers with a diameter of about 160-280 nm, and no composite modified activated carbon material particles can be observed on the surface of the composite membrane material.

[0110] The membrane materials prepared in Examples 1-3 and Comparative Examples 1-4 were subjected to contact angle tests. The contact angle of the membrane was detected by a contact angle measuring instrument. The test liquid was dropped onto the membrane surface, and the shape of the droplet was recorded by an optical imaging system. The contact angle of the liquid on the membrane surface was calculated by using the circular arc fitting method. The test results are shown in Table 1.

[0111] Table 1. Contact angle test results for different groups

[0112]

[0113] As can be seen from Table 1, compared with Comparative Examples 1-4, the membrane material prepared in the embodiments of the present invention exhibits superior hydrophilicity and oleophobicity, with a water contact angle of 2.9° and an underwater oil contact angle of 163.2°. By comparing Examples 1-3, it can be seen that as the amount of added composite modified activated carbon material increases, the underwater oleophobic performance of the prepared membrane shows a process of first increasing and then slowly increasing. Based on this, it can be inferred that the amount of added composite modified activated carbon material affects the underwater oleophobicity of the membrane material.

[0114] The underwater superoleophobic properties also enhance the membrane's antifouling ability to some extent. To simulate the impact of oil during wastewater treatment, the membrane material prepared in Example 1 was used for testing. Figure 2 As shown, using dichloromethane dyed with Sudan I, oil droplets were dropped onto a tilted membrane material in water using a syringe. Upon impact with the membrane surface after being removed from the needle, the oil droplets were first compressed into an elliptical shape, then bounced up and began to roll upon contact with the membrane, leaving no oil stains on the membrane surface. This is because once the membrane combines with water to form an aqueous layer, the oil cannot easily contact the membrane surface, preventing the accumulation of oil droplets on the membrane, exhibiting good self-cleaning ability, and extending the membrane's service life.

[0115] Oil-water separation test

[0116] The oil phase (n-hexane):water phase was mixed at a volume ratio of 1:9. Tween 80 was used as the surfactant. Sudan I dyed oil phase was added, and the mixture was stirred at 500 rpm for 2 hours, sonicated for 2 hours, and allowed to stand for 1 hour to prevent the emulsion from separating, thus obtaining an oil-in-water emulsion. Figure 3The device shown carries out the test, respectively, the membrane material is clamped in the filter cup and the glass sand core, and is fixed with the clamp, the triangular flask is connected with the glass sand core for bearing the filtrate, the circulating water vacuum pump is connected with the glass sand core, and the oil-in-water emulsion is poured into the filter cup, the vacuum pump is opened, under the action of pressure, the emulsion passes through the membrane to the suction flask below, the membrane material is carried out 20 times of oil-water separation cycle test according to the above steps, the water flux and separation efficiency of the 20th time are calculated, and the results are shown in table 2.

[0117] Table 2 oil-water separation performance test results of different groups

[0118]

[0119] As can be seen from table 2, after 20 times of cycle use test, the water flux of the membrane material prepared by the embodiment of the application can still reach 34.6 L / (m 2 ·h), and the separation efficiency can still reach 99.8%, compared with comparative examples 1-4, the separation efficiency of the membrane material prepared by the application is higher, and the separation effect is better, and the reason may be that when the oil-in-water emulsion contacts the membrane surface, because the water content is high, the hydrophilic surface is first wetted by water and forms a water film, and the formation of the water film prevents the oil droplets from contacting the membrane surface; at the same time, the water phase in the emulsion is the continuous phase, and the water phase can quickly pass through the gap of the membrane, but the blocked oil droplets are disturbed by external force and collide constantly in the process, so that multiple small oil droplets are aggregated and fused, at this time, the stability of the emulsion is broken, and small oil droplets gradually form larger oil droplets, and larger oil droplets are more easily intercepted by the membrane, so that the purpose of oil-water separation is achieved.

[0120] The separation effect of the composite membrane material prepared in example 1 of the application on the oil-in-water emulsion is shown in the figure as Figure 4 shown, from the figure, it can be seen that the original emulsion is milky white, and the filtrate becomes transparent and clear after being separated by the composite membrane material.

[0121] Finally, it should be noted that the above examples do not limit the application in any form. For those skilled in the art, some modifications and improvements can be made on the basis of the application. Therefore, any modification or improvement made without departing from the spirit of the application shall fall within the scope of the application claimed.

Claims

1. A method for preparing a composite membrane material for oil-water separation, characterized in that, Comprising the following steps: S1, dispersing the pretreated activated carbon in an aqueous ethanol solution, then adding an amino silane coupling agent thereto, stirring, and then filtering, washing, and drying to obtain an amino-modified activated carbon; S2, dissolving an iron salt, a lanthanum salt, and an organic ligand in an organic solvent, then adding the amino-modified activated carbon thereto, ultrasonic dispersion, hydrothermal reaction, centrifugation, washing, and drying to obtain an activated carbon / MOF composite material; S3, mixing the activated carbon / MOF composite material and a tannic acid solution, and then performing ball milling to obtain a composite modified activated carbon material; S4, preparing a PVA solution, then adding the composite modified activated carbon material thereto, ultrasonic dispersion, and then electrospinning to obtain a fiber membrane; S5, crosslinking the fiber membrane in a glutaraldehyde vapor to obtain a composite membrane material for oil-water separation.

2. The production method according to claim 1, characterized by, In step S1, the pretreated activated carbon is prepared by immersing activated carbon in a nitric acid solution, heating and stirring, and then washing and drying.

3. The preparation method according to claim 1, characterized in that, In step S1, the mass ratio of the pretreated activated carbon to the amino silane coupling agent is 4-8:1-2.

4. The method of claim 1, wherein, In step S2, the amount ratio of the iron salt, the lanthanum salt, the organic ligand, and the amino-modified activated carbon is 1-2 mmol:0.2-0.5 mmol:2-4 mmol:2-5 g.

5. The preparation method according to claim 1, characterized in that, In step S2, the temperature of the hydrothermal reaction is 150-180℃, and the time of the hydrothermal reaction is 4-8 h.

6. The method of claim 1, wherein, In step S3, the mass ratio of the activated carbon / MOF composite material to the tannic acid solution is 10-15:20-30.

7. The preparation method according to claim 1, characterized in that, In step S3, the mass fraction of the tannic acid solution is 2-5%.

8. The method of claim 1, wherein, In step S4, the amount ratio of the PVA solution to the composite modified activated carbon material is 10 mL:0.01-0.1 g.

9. The method of claim 1, wherein, In step S4, the mass fraction of the PVA solution is 5-10%.

10. The composite membrane material for oil-water separation prepared by the preparation method of any one of claims 1-9.

Citation Information

Patent Citations

  • An oil-water separation material based on electrospun / PVA composite hydrogel and its preparation method

    CN113457218B

  • Method for removing arsenic by using carbon-based Fe / La-metal organic framework composite adsorbent

    CN118437298A

  • Janus composite for oil in water separation

    US20230212037A1